Effect of Eugenol on Preservation and Quality of Passion Fruit - BA Liangjie, SUN Yanzheng, LUO Donglan, CHEN Jianye (Shipin Kexue, 2023)
In an attempt to evaluate the effect of eugenol on the preservation and quality of passion fruit, its physiological and biochemical changes were investigated after soaking treatment with 0.3 mg/mL at room temperature, (20 ± 1) ℃. The results showed that eugenol treatment reduced the postharvest respiratory rate, mass loss rate, shrinkage index and cell membrane permeability, inhibited the accumulation of malondialdehyde (MDA), superoxide anion radical and hydrogen peroxide, slowed down the decrease in the contents of soluble solids, soluble proteins, total phenols and flavonoids and maintained high contents of endogenous antioxidant substances such as reduced ascorbic acid (AsA) and reduced glutathione (GSH) in passion fruit. It also maintained high scavenging capacity against 1,1-diphenyl-2-picrylhydrazyl (DPPH), hydroxyl radical, 2,2’-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) radical cation and ferric reducing capacity, and improved the activities of antioxidant enzymes such as catalase (CAT), superoxide dismutase (SOD), and ascorbate peroxidase (APX). In summary, eugenol treatment can maintain high quality and antioxidant activity of postharvest passion fruit, thereby delaying fruit senescence and extending the storage period.